2010
DOI: 10.1021/es902883a
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Body Burdens of PBDEs, Dioxins, and PCBs on Thyroid Hormone Homeostasis at an Electronic Waste Recycling Site in China

Abstract: A cross-sectional study of 25 sample sets (each set consisted of maternal serum and cord whole blood) from 50 pregnant women in zone A (n = 25 from exposed group) and zone B (n = 25 from reference group) was conducted to examine the association between thyroid hormone (TH) levels and PBDE, PCDD/F, and PCB exposures. Thyroid hormones TT3, TT4, and TSH levels were measured in maternal serum at 16 weeks of gestation. The concentrations of PBDEs, PCDD/Fs, and PCBs were determined by isotope dilution HRGC/HRMS in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(46 citation statements)
references
References 41 publications
5
41
0
Order By: Relevance
“…Similar to the findings of our previous study (Lin et al, 2011), in a cohort study of infants born in the US indicates negative associations between cord blood levels of BDE-100 and BDE-153 and cord blood values of total T4 and FT3 (Herbstman et al, 2008). In contrast, several human studies that assess the associations between PBDEs and thyroid hormones in cord blood find no significant relation ( Mazdai et al, 2003;Kim et al, 2009;Zhang et al, 2010;Chevrier et al, 2011;Gascon et al, 2011;Kim et al, 2011). Specifically, Kim et al (2009) finds no apparent relationship between fetal T4 and cordblood PBDEs in 108 Korean infants.…”
Section: Pbdes and Thyroid Hormonessupporting
confidence: 82%
See 3 more Smart Citations
“…Similar to the findings of our previous study (Lin et al, 2011), in a cohort study of infants born in the US indicates negative associations between cord blood levels of BDE-100 and BDE-153 and cord blood values of total T4 and FT3 (Herbstman et al, 2008). In contrast, several human studies that assess the associations between PBDEs and thyroid hormones in cord blood find no significant relation ( Mazdai et al, 2003;Kim et al, 2009;Zhang et al, 2010;Chevrier et al, 2011;Gascon et al, 2011;Kim et al, 2011). Specifically, Kim et al (2009) finds no apparent relationship between fetal T4 and cordblood PBDEs in 108 Korean infants.…”
Section: Pbdes and Thyroid Hormonessupporting
confidence: 82%
“…Contrary to the above findings, a Dutch study finds that cord blood T3 level have significantly positive correlation with maternal serum levels of BDE-47, BDE-99, and BDE-100 in the 35th week of pregnancy (Roze et al, 2009). Most current epidemiological studies, including our previous study, have not found any relationship between prenatal exposure to PBDEs and cord blood TSH level (Herbstman et al, 2008;Kim et al, 2009;Roze et al, 2009;Zhang et al, 2010;Chevrier et al, 2011;Lin et al, 2011).…”
Section: Pbdes and Thyroid Hormonesmentioning
confidence: 62%
See 2 more Smart Citations
“…Abundant toxins, such as trace metals, polybrominated diphenyl ethers (PBDEs), and PCBs have been released into the environment due to use of primitive e-waste recycling processes [1][2][3][4][5][6][7][8]. High levels of persistent organic pollutants (POPs) and trace metals have been detected in the air, dust, soil, sediment, and biota samples around e-waste recycling sites, which may pose a threat to local residents and the ecosystem [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%